A Cross Sectional Survey of Kidney Transplatation Cost - Dulal, Ram Krishna; Karki, S.; Dahal, A. (Journal of Nepal Health Research Council, 2009)
Not uploaded.Key words: Cost; Hemodialysis; TransplantationDOI: 10.3126/jnhrc.v6i1.2437Journal of Nepal Health Research Council Vol. 6, No. 1, Issue 12, April, 2008 Page: 5-10